Training and mentoring for corn-based food processing in Sillu Village, Kupang - Zainal Abidin; Titik Sri Harini; Hironnymus Jati; Lewi Jutomo (Community Empowerment, 2022)
Sillu Village farmers' corn commodity has a very low economic added value, so their income is low. This is due to a lack of quantity and quality processed products, which are not supported by TTG, unappealing product packaging and labeling, a lack of P-IRT, and poor organization and management. The solution includes the setup of marning production using TTG with SOPs covering input, process, and output; packaging and marketing; packaging and labeling design; organization and management setup; and the search for new markets, as well as the management of P-IRT and halal certificates. Lectures, the practice of making corn-based processed food variants, procurement of production equipment, improvement of organizational structure and business management, distribution permit management (P-IRT, halal certificate), laboratory testing, and digital marketing are among the methods used in the approach. Increased partner awareness of the importance and management of P-IRT, good corn-based processed food production processes, mastery of TTG, halal-certified and labeled marning products, improved organizational and management formations, and availability of financial records and inventory are among the outcomes obtained.